Parental stress and nurse-parent support in the neonatal intensive care unit: a cross-sectional study - Dilek Konukbay; Mürşide Vural; Dilek Yildiz (BMC, 2024)
Abstract Background Admission of a preterm infant to the Neonatal Intensive Care Unit (NICU) is highly stressful for parents. NICU nurses play a crucial role in providing support, positively impacting health and aiding effective stress management during this challenging period. This study assesses stress and nurse-parent support for parents with preterm infants in the NICU, exploring connections between stress, support, and various parental and infant variables. Methods This descriptive cross-sectional study was conducted between January and July 2019 on a total of 150 parents (75 mothers and 75 fathers) with preterm infants in a private hospital's NICU in Ankara, Turkey. Data were collected using the Parent and Infant Information Form, Parental Stressor Scale: NICU (PSS: NICU), and Nurse-Parent Support Tool (NPST). Results There was no significant correlation between PSS: NICU and NPST scores (p > 0.05). However, a significant difference was observed in the overall NPST score (p = 0.036) and its emotional support subscale (p = 0.013). Mothers' PSS: NICU was influenced by infant information (p = 0.027) and marital duration ((p = 0.002), while fathers' was influenced by number of children (p = 0.040) and infant care participation (p = 0.001). NPST was affected by number of children (p = 0.004) and infant respiratory status (p = 0.011) for mothers and number of children for fathers (p = 0.038). Since parents require informational, emotional, and care-related support, nurses should continuously enhance their professional and communication skills to establish effective communication with parents and provide targeted support. Conclusion This study found mothers received greater nurse support than fathers. Mothers with one child had higher nurse support, while mechanical ventilation for mothers and having more than one child for fathers were linked to reduced support. Lower stress levels were noted in mothers married for 6-10 years, those informed about the infant, and fathers actively participating in infant care with more than one child.